LA FILOSOFÍA APLICADA EN EL TERREMOTO JAPONÉS DE 2011. UNA ENTREVISTA CON EL PROF. TETSUYA KONO - Kono, Tetsuya; Barrientos-Rastrojo, José (Revista Internacional de Filosofía Aplicada HASER, 2021)
Interview to Tetsuya Kono related to the activity of Philosophical Practitioners in the Jappanesse 2011 Earthquake